A literatura contra o autoritarismo: a desordem social como princípio da fragmentação na ficção brasileira pós-64 - Calegari, Lizandro Carlos (2008)
A reflection on the fragmentation in various works produced during the period of the 1964-85 dictatorship in Brazil is the purpose of this dissertation: Zero, by Ignácio de Loyola Brandão; A festa, by Ivan Ângelo; Reflexos do baile, by Antonio Callado and Quatro-olhos, by Renato Pompeu. The first novel was completed in 1969 and published in 1975; the other three were published in 1976. The overall goal consists of demonstrating that formal fragmentation is, in varying ways, tied to the social disorder of the historical moment in question. Moreover, this disorder on the sociohistorical plane considered here from a broad perspective exists in a dialogue with a background based on an authoritarian practice and/or an authoritarian ideology. Thus, among the diverse aspects studied, emphasis is given to theories of the novel, as well as to theoretical and thematic points that related to the problem identified by the investigation. In this sense, in Brandão s book, there is an analysis of topics like the constitution of the subject and literary carnivalization. In Ivan Ângelo, discussion turns on the markers of authoritarianism in Brazilian society and the polyphony of the text. In Callado, there is an in-depth consideration of historical markers, as well as satirical, parodic and comic elements. Pompeu s text is privileged in terms of abulia and memory loss, along with melancholy. The subject at hand is important because, at the present moment, there is a realization of the nightmares formulated in the 30s and 40s regarding dehumanization. In order to deal adequately with these matters, support has been sought in references on theories of the novel, social history and the sociology of literature, bearing in mind authors prominent in the Frankfurt School. Additionally, elements drawn from literary theory, beginning with comparative literature, have been taken into account, along with interdisciplinary perspectives drawn from other areas of knowledge.